Band alignment and enhanced breakdown field of simultaneously oxidized and nitrided Zr film on Si - Wong, Y.H.; Cheong, K.Y. (SpringerOpen, 2011)
The band alignment of ZrO2/interfacial layer/Si structure fabricated by simultaneous oxidation and nitridation of sputtered Zr on Si in N2O at 700°C for different durations has been established by using X-ray photoelectron spectroscopy. Valence band offset of ZrO2/Si was found to be 4.75 eV, while the highest corresponding conduction offset of ZrO2/interfacial layer was found to be 3.40 eV; owing to the combination of relatively larger bandgaps, it enhanced electrical breakdown field to 13.6 MV/cm at 10-6 A/cm2.